Biology of Cellulosic Bacteria from Hindgut Oryctes rhinoceros as Antagonistic Agent of Ganoderma boninense In Vitro - Purba, Vita Mutiara Rizky; Marheni, Marheni (Department of Agronomy and Horticulture, IPB University, 2025)
Ganoderma boninense is a pathogenic fungus that causes the base rot of oil palm trunks. Antagonistic microorganisms can inhibit, suppress, or eliminate populations of plant pathogens. Antagonistic microorganisms can be utilized through symbiotic bacteria. The capability of symbiotic bacteria to degrade cellulose enables them to be more utilized as biological agents for controlling plant pathogens. Oryctes rhinoceros larvae are one of the insects that have symbiotic bacteria. This study aims to analyze the morphological and biochemical characteristics of symbiotic bacteria of O. rhinoceros larvae and see their effectiveness in inhibiting the growth of G. boninense. This research employed a non-factorial completely randomized design with six treatments: S0, Ganoderma boninense (control); S1, G. boninense + isolate of symbiotic bacteria (P2); and S2, G. boninense + isolate of symbiotic bacteria (P3). The results showed that treatment P2 that c, which contains Bacillus subtilis, was able to inhibit G. boninense by 35.21%, and the P3 bacterial isolate, which is Bacillus sp., was able to inhibit the growth of G. boninense by 23.66%. The identification showed that bacteria P2 is B. subtilis, and P3 is Bacillus sp.